2013
DOI: 10.1186/1472-6807-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the S100A4/myosin-IIA complex

Abstract: BackgroundS100A4, a member of the S100 family of Ca2+-binding proteins, modulates the motility of both non-transformed and cancer cells by regulating the localization and stability of cellular protrusions. Biochemical studies have demonstrated that S100A4 binds to the C-terminal end of the myosin-IIA heavy chain coiled-coil and disassembles myosin-IIA filaments; however, the mechanism by which S100A4 mediates myosin-IIA depolymerization is not well understood.ResultsWe determined the X-ray crystal structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
1
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 54 publications
4
27
1
5
Order By: Relevance
“…[14,27,43] The 1 H, 15 NH SQC spectrum of S100A4dCh as well-dispersed resonances, as expectedf or af olded protein. ACterminally 13 residues truncated form of Ca 2 + -bound S100A4 (S100A4dC) wasu sed, in order to avoid the aggregation tendency of full-length S100A4.P revious studies indicated that MPT binding is not affectedb yt his C-terminal truncation.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…[14,27,43] The 1 H, 15 NH SQC spectrum of S100A4dCh as well-dispersed resonances, as expectedf or af olded protein. ACterminally 13 residues truncated form of Ca 2 + -bound S100A4 (S100A4dC) wasu sed, in order to avoid the aggregation tendency of full-length S100A4.P revious studies indicated that MPT binding is not affectedb yt his C-terminal truncation.…”
Section: Resultssupporting
confidence: 64%
“…[9][10][11][12][13][14] All the distinctive structural elements characteristic for S100 proteins are present:t he pseudo-EF hand near the Nterminus (formed by helicesH 1a nd H2, which surround loop L1), ac onnecting "hinge" (L2) and the canonical EF-handc lose to the Cterminus (L3 loop flankedb y helices H3 and H4). [9][10][11][12][13][14] All the distinctive structural elements characteristic for S100 proteins are present:t he pseudo-EF hand near the Nterminus (formed by helicesH 1a nd H2, which surround loop L1), ac onnecting "hinge" (L2) and the canonical EF-handc lose to the Cterminus (L3 loop flankedb y helices H3 and H4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore we solved the crystal structure of Ca 2+ -saturated Δ13 mutant in complex with MPT peptide (Supporting information, Figure S6, Table S4), which apart from some differences observed (Supporting information, Figure S7), essentially confirmed the asymmetric binding mode of MPT observed in complexes of the full length protein [7], [8] and Δ8 C-terminal truncated mutant [9].…”
Section: Resultssupporting
confidence: 59%
“…As a consequence, target binding is typically Ca 2+ -dependent. Importantly, the three-dimensional structures of S100–target complexes have revealed that individual family members exhibit distinct modes of target recognition owing, in part, to differences in surface geometries, hydrophobic residue distribution and charge density 25 . In addition, some family members undergo a variety of post-translational modifications, such as oxidative modification and sumoylation, which can modulate S100–target complex formation and/or intracellular localization 2629 .…”
Section: Conformation and Structurementioning
confidence: 99%